Analysing the factor structure of the MAIA scale for pregnant women: Development of the MAIA-Preg - Anna E. Crossland; Lydia B. Munns; Catherine E. J. Preston (PLoS ONE, 2025)
During pregnancy many elements of the bodily experience change, suggesting that measuring these constructs may require different instruments to those validated in the general population. This study reports an exploratory and confirmatory factor analysis exploration of the Multidimensional Assessment of Interoceptive Awareness (MAIA) in 716 pregnant women (mean gestation 26.4 weeks), from six different datasets who completed the MAIA online. Exploratory factor analysis condensed the questionnaire from a 32- to a 19- item scale, with five factor structure, which best fitted the data. Key subscales of Trust, Attention Regulation, Self-Regulation and Not Distracting remained robust. The one remaining item from the Noticing subscale loaded heavily with the Emotional Awareness subscale. Subscales of Body Listening, Not Worrying and Noticing did not load and therefore were excluded as factors. This led to the development of the scale referred to as the MAIA-Preg, which demonstrated a good fit with a confirmatory factor analysis along with good subscale reliability (ω= 0.73 -0.92), and measurement invariance for second and third trimesters. The MAIA-Preg was also found to be a good fit for separate non-pregnant (N = 396) and postnatal (N = 174) samples and thus provides a reliable and valid measure, providing nuanced information about the bodily experience in perinatal populations, allowing comparisons of changes to interoceptive sensibility the perinatal period.